(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the activities of hospitals in Andijan region, achievements and problems in their construction and repair, provision of clean drinking water, telephone network, modern diagnostic and treatment equipment, and the loan funds allocated by the World Bank for these works.